Methanobacterium Capable of Direct Interspecies Electron Transfer - Zheng, Shiling; Liu, Fanghua; Wang, Bingchen; Zhang, Yuechao; Lovley, Derek R (Environmental science & technology, 2020)
Direct interspecies electron transfer (DIET) from bacteria to methanogens is a revolutionary concept for syntrophic metabolism in methanogenic soils/sediments and anaerobic digestion. Previous studies have indicated that the potential for DIET is limited to methanogens in the Methanosarcinales, leading to the assumption that an abundance of other types of methanogens, such as Methanobacterium species, indicates a lack of DIET. We report here on a strain of Methanobacterium, designated strain YSL, that grows via DIET in defined cocultures with Geobacter metallireducens. The cocultures formed aggregates, in which cells of strain YSL and G. metallireducens were uniformly dispersed throughout. This close association of the two species is the likely explanation for the ability of a strain of G. metallireducens that could not express electrically conductive pili to grow in coculture with strain YSL. Granular activated carbon promoted the initial formation of the DIET-based cocultures. The discovery of DIET in Methanobacterium, the genus of methanogens that has been the exemplar for interspecies electron transfer via H2, suggests that the capacity for DIET is much more broadly distributed among methanogens than previously considered. More innovative approaches to microbial isolation and characterization are needed in order to better understand how methanogenic communities function.